Stainless steel having excellent surface properties

JP2025030200AActive Publication Date: 2025-03-07NIPPON YAKIN IND KK
View PDF 40 Cites 0 Cited by

Patent Information

Application Number
JP2023135284
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2025-03-07
Estimated Expiration
2043-08-23

AI Technical Summary

Benefits of technology

【0022】 また、上記のMgO·Al2O3はMnOを0.5%以下含んでも良い。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025030200000001_ABST
    Figure 2025030200000001_ABST
Patent Text Reader

Abstract

To provide a stainless steel having sound surface properties without surface defects by comprehensively considering the control of the composition and structural formation of non-metallic inclusions, and a method for producing the same.SOLUTION: There is provided a stainless steel having excellent surface properties which comprises, by mass%, 0.001 to 0.3% of C, 0.1 to 4% of S, 0.1 to 3% of Mn, 0.05% or less of P, 0.03% or less of S, 4 to 40% of Ni,13 to 35% of Cr, 0.1 to 8% of Mo, 0.1 to 4% of Cu, 0.001 to 0.5% of Al, 0.6% or less of Ti, 0.0001 to 0.02% of Ca, 0.0001 to 0.02% of Mg, 0.001 to 0.4% of N, 0.01% or less of O, 4% or less of one or two or more of Co, W, Nb and B, the balance iron, and inevitable impurities, wherein the average composition of non-metallic inclusions is 30 to 70% of MgO, 15 to 40% of Al2O3, 30% or less of SiO2, 10 to 40% of CaO, and 1% less of MnO.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an austenitic stainless steel, a duplex stainless steel, a precipitation hardening stainless steel, a heat resistant steel, and a highly wear resistant stainless steel having excellent surface properties, and to a method for producing the same. [Background technology]

[0002] Austenitic stainless steels are widely used in society due to their high corrosion resistance and excellent workability. In particular, in recent years, as hydrogen utilization toward carbon neutrality has progressed, the low temperature resistance of austenitic stainless steels has attracted attention (for example, see Patent Documents 1 to 4).

[0003] Duplex stainless steel is characterized by its tendency to have fine crystal grains because it is composed of austenite and ferrite phases. Therefore, it has the advantage of being not only highly corrosion resistant but also strong, and since the strength can be maintained even in thin plates, it has excellent cost performance (for example, see Patent Documents 5 to 11).

[0004] Precipitation hardening stainless steel is an alloy that is strengthened by forming a fine second phase through aging treatment, and is widely used for steel belts and the like (see, for example, Patent Documents 12 to 16).

[0005] Furthermore, stainless steel also has heat resistance and is often used in high-temperature corrosive environments. In recent years, it has been widely used in reactors for manufacturing solar-grade silicon elements for photovoltaic power generation (see, for example, Patent Documents 17 to 23).

[0006] Wear-resistant stainless steels are used in devices that generate friction. By increasing the C content and optimizing the Cr content, an appropriate amount of Cr carbide can be precipitated, which increases wear resistance. Stainless steels are sometimes used for reeds and healds in weaving machines (see, for example, Patent Documents 24 to 26).

[0007] In addition to the above, stainless steel is also used in turbochargers and exhaust manifolds, which are components of exhaust gas systems for automobiles. This is because stainless steel has excellent heat resistance and is resistant to corrosion. Furthermore, in automobiles equipped with diesel engines, so-called exhaust gas recirculation devices (hereinafter referred to as "EGR") have been developed and put into practical use, which return part of the exhaust gas to the intake system, lowering the maximum temperature when the mixture is burned and suppressing the amount of NOx generated, and stainless steel is also used in these devices (see, for example, Patent Documents 27 to 30).

[0008] Since these stainless steels and alloy steels are used without surface treatment such as painting, their surface properties are extremely important. Many high-purity technologies have been disclosed so far. That is, technologies have been disclosed that precisely control the composition of nonmetallic inclusions to render them harmless. Alternatively, technologies have been disclosed that reduce their number (see, for example, Patent Documents 31 to 36).

[0009] However, it is difficult to say that defects can be completely prevented by simply controlling the composition of nonmetallic inclusions, and there is a problem in that the inclusion particles may not be rendered harmless depending on their structure. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2019-143227 A [Patent Document 2] WO2012 / 043877 publication [Patent Document 3] WO2018 / 180778 publication [Patent Document 4] Patent Publication No. 2021-167455 [Patent Document 5] Patent Publication No. 2021-155827 [Patent Document 6] Patent Publication No. 2021-188123 [Patent Document 7] Patent Publication No. 2021-75771 [Patent Document 8] JP 2020-100872 A [Patent Document 9] Patent Publication No. 2021-31757 [Patent Document 10] JP 2022-98633 A [Patent Document 11] JP 2009-007638 A [Patent Document 12] Patent No. 7274062 [Patent Document 13] Patent No. 7029570 [Patent Document 14] Patent No. 7018537 [Patent Document 15] Patent No. 6776467 [Patent Document 16] JP 2017-155317 A [Patent Document 17] Patent No. 7187604 [Patent Document 18] Patent No. 7187605 [Patent Document 19] Patent No. 7187606 [Patent Document 20] Patent Publication No. 2021-70838 [Patent Document 21] JP 2018-059148 A [Patent Document 22] JP 2014-189826 A [Patent Document 23] Patent No. 7174192 [Patent Document 24] JP 2004-18935 A [Patent Document 25] JP 2003-147493 A [Patent Document 26] JP 2003-105504 A [Patent Document 27] JP 2014-034694 A [Patent Document 28] JP 2022-98633 A [Patent Document 29] Patent Publication No. 2021-4577 [Patent Document 30] Patent No. 6547011 [Patent Document 31] Patent No. 6903182 [Patent Document 32] Patent No. 6762414 [Patent Document 33] JP 2020-033579 A [Patent Document 34] JP 2015-74807 A [Patent Document 35] JP 2004-149830 A [Patent Document 36] JP 2004-149833 A Summary of the Invention [Problem to be solved by the invention]

[0011] The main aim of the present invention is to prevent the clustering of nonmetallic inclusions, which can cause large surface defects, by controlling not only the composition of the nonmetallic inclusions but also their structure, as described above. At the same time, the formation of CaO inclusions and Al2O3 inclusions must be prevented because they tend to cluster. Furthermore, MnO-Cr2O3 inclusions must be prevented because they form in an environment with a high oxygen concentration, resulting in a large number of inclusions in total and a tendency to cluster.

[0012] That is, an object of the present invention is to comprehensively consider the above and to provide a stainless steel having a sound surface quality free of surface defects, and a method for manufacturing the same. [Means for solving the problem]

[0013] In order to solve the problems of the above-mentioned conventional techniques, the inventors have repeatedly carried out intensive experiments as described below.

[0014] First, 20 kg of Fe-35%Ni-23Cr-7.7%Mo-3%Cu-0.2%N alloy was melted in a magnesia crucible in the laboratory. A high-frequency induction furnace was used as the melting equipment, and argon gas was blown from above the crucible to isolate it from the atmosphere. The raw materials used were electrolytic iron, ferrochrome, Mo, copper wire, and ferrochrome nitride. Finally, Si and Al were added to deoxidize the alloy, and 1 kg of artificial slag of CaO-Al2O3-MgO-SiO2-F system was added, and the composition of the nonmetallic inclusions was carefully observed by sampling. The observation was performed using SEM. The analysis was performed using EDS. In particular, elemental mapping was performed carefully, and the structural morphology was carefully observed. It was found that to find the compositional characteristics, at least 10 inclusions need to be analyzed, 20 is better, and 30 or more is sufficient.

[0015] The steel ingots cast into the molds were forged to a thickness of 20 mm, after which the surfaces were ground and cold rolled. The final plate thickness was 0.5 mm, and the surfaces were carefully observed to determine whether there were any defects.

[0016] As a result, it was found that the occurrence of defects is strongly related to the structural morphology of nonmetallic inclusions, and that a structural morphology in which CaO-Al2O3-MgO oxides contain MgO or MgO·Al2O3 has a high ability to suppress clustering. A schematic diagram of this is shown in Figure 1. Figure 1(a) shows a CaO-Al2O3-MgO oxide that completely contains MgO or MgO·Al2O3 within its approximately spherical surface, which is a good morphology that can suppress clustering. On the other hand, it was revealed that a morphology in which part of the outer edge is CaO-Al2O3-MgO, and most of the inside is high-melting point MgO or MgO·Al2O3 oxides that protrude from the approximately spherical surface of the inclusion, as shown in Figure 1(b), promotes clustering. Although the mechanism is largely unknown, it is assumed that the CaO-Al2O3-MgO melt acts as a sintering aid at steelmaking temperatures (1400-1550°C), adhering to each other and sintering. Based on experience, it has been assumed that the main sintering location is the inner wall of the submerged nozzle of the continuous casting machine.

[0017] On the other hand, it was also confirmed that sintering does not occur when MgO·Al2O3 or MgO is used alone. It became clear that the structure of the surrounding CaO-Al2O3-MgO oxide melt has a large effect on the final quality.

[0018] With this, for some steel types, the raw materials were melted in a 70-ton electric furnace, decarburized in an AOD, quicklime was added from above while FeSi was added at the same time, Cr reduction was performed, and then Al was added to proceed with deoxidization and desulfurization for refining. After that, slabs were produced in a continuous casting machine, and after surface grinding, they were hot rolled, cold rolled, and finally passed through the annealing and pickling line to produce 0.5 mm thick thin plates.

[0019] That is, the present invention was developed based on the above laboratory studies and through confirmation by actual equipment testing, as described below. The chemical compositions are all in mass percent: C: 0.001-0.3%, Si: 0.1-4%, Mn: 0.1-3%, P: 0.05% or less, S: 0.03% or less, Ni: 4-40%, Cr: 13-35%, Mo: 0.1-8%, Cu: 0.1-4%, Al: 0.001-0.5%, Ti: 0.6% or less, Ca: 0.0001-0.02%, Mg: 0.0001-0. It contains 02%, N: 0.001-0.4%, O: 0.01% or less, 4% or less of one or more of Co, W, Nb, and B, with the balance being iron and unavoidable impurities, and the average composition of non-metallic inclusions is MgO: 30-70%, Al2O3: 15-40%, SiO2: 30% or less, CaO: 10-40%, MnO: 1% or less, and it is a stainless steel with excellent surface properties. In other words, it is a stainless steel with no defects on the surface.

[0020] Furthermore, in a more preferred embodiment, the structural form of the nonmetallic inclusions is such that 70% or more of the nonmetallic inclusions in terms of number ratio to the total nonmetallic inclusions are any one or more of the following five types a to e. a: CaO-Al2O3-MgO oxide completely encloses MgO·Al2O3 within a roughly spherical surface b: CaO-Al2O3-MgO oxide c: CaO-Al2O3-MgO oxide completely encloses MgO within a roughly spherical surface d: MgO alone e: MgO·Al2O3 alone

[0021] Further, in a more preferred embodiment, the CaO-Al2O3-MgO oxide has a composition of CaO: 20-60%, Al2O3: 30-60%, MgO: 1-30%, SiO2: 20% or less, and TiO2: 0.5% or less.

[0022] Moreover, the above MgO·Al2O3 may contain 0.5% or less of MnO.

[0023] In a preferred embodiment, the above-mentioned simple MgO contains Al2O3: 3% or less, SiO2: 1% or less, CaO: 10% or less, and MnO: 1% or less.

[0024] The present invention also provides a manufacturing method. That is, the raw materials are melted in an electric furnace, then decarburized and refined in an AOD, quicklime and FeSi are added to perform Cr reduction, and Al is further added to form a CaO-Al2O3-MgO-SiO2-F slag, which is then deoxidized and desulfurized, and a slab is produced in a continuous casting machine, the surface is ground, and the slab is subjected to a hot rolling process and then cold rolling. At this time, it can be said that it is necessary to control the slag composition within an appropriate range in order to control the structural form of the nonmetallic inclusions to a preferable form. [Brief description of the drawings]

[0025]

Figure 1

Figure 2

[0026] The reasons for the numerical limitations of the present invention and the scientific viewpoints thereof will be explained below. The units below are % by mass. C: 0.001 to 0.3% C is an important element for maintaining the strength of stainless steel and for improving wear resistance by forming carbides with Cr. Therefore, 0.001% is necessary. On the other hand, adding more than 0.3% has the drawback of forming carbides of Ti, Nb, etc., which leads to embrittlement. Therefore, the content is specified as 0.001 to 0.3%. The addition is controlled by adding pig iron after desulfurization in the AOD. The content is preferably 0.002 to 0.025%, and more preferably 0.005 to 0.22%.

[0027] Silicon: 0.1 to 4% In addition to being effective in deoxidation, silicon is an element that improves heat resistance and is very important in the present invention. Deoxidation can be carried out according to the following formula. In other words, in AOD, FeSi alloy is added to the Cr reduction. Si +2 O =(SiO2) …(1) Here, the underlined parts are the components in the molten steel, and the parentheses are the components in the slag. As will be described later, by lowering the activity coefficient of SiO2 in the slag, deoxidation can be effectively promoted and the oxygen concentration can be controlled to the oxygen concentration of the present invention. Furthermore, desulfurization can be performed at the same time. 0.1% is necessary to achieve this effect, and if it exceeds 4%, a σ phase is formed, which not only reduces the corrosion resistance but also causes embrittlement. Therefore, the range is specified as 0.1 to 4%. The range is preferably 0.15 to 3.8%, and more preferably 0.18 to 3.5%.

[0028] Mn: 0.1-3% Mn is an element useful for deoxidization, and is also an extremely effective element for stabilizing the austenite phase, and therefore is specified to be 0.1 to 3%, preferably 0.2 to 2.6%, and more preferably 0.3 to 2.5%.

[0029] P:0.05% or less P is a harmful element that not only segregates at grain boundaries and reduces corrosion resistance, but also causes red brittleness during welding, leading to cracking. Therefore, the P content is set to 0.05% or less, preferably 0.04% or less, and more preferably 0.035% or less.

[0030] S: 0.03% or less S is a harmful element because it segregates at grain boundaries and forms MnS, which becomes the starting point of pitting corrosion. It also reduces hot workability and causes edge cracks. Therefore, the content is set at 0.03% or less. As will be described in detail later, desulfurization can be promoted by the following reaction formula. 3(CaO)+2 Al +3 S =(Al2O3)+3(CaS) …(2) 2(CaO)+ Si +2 S =(SiO2)+2(CaS) …(3) The desulfurization reaction can be promoted efficiently by decreasing the activity coefficient of alumina and silica in the slag. The above problems can be avoided if the content is 0.03% or less, so it is set within this range. The content is preferably 0.02%, more preferably 0.01% or less, and even more preferably 0.008% or less.

[0031] Ni: 4~40% Ni is a major element in the present invention, and is an important element for stabilizing the austenite phase and improving workability. If it is less than 4%, in the case of duplex stainless steel, the ferrite phase will exceed 50% and become too large. If it is 40% or more, the stability of the structure will be impaired. Therefore, it is specified to be 4 to 40%. It is preferably 5 to 39%, more preferably 6 to 38.8%, and even more preferably 7 to 38.7%.

[0032] Cr: 13~35% Cr is a major element in the present invention, and is essential for forming a dense passive film on the surface of stainless steel to maintain corrosion resistance. For this reason, the content is specified as 13 to 35%. It is preferably 14 to 34%, more preferably 14.5 to 33%, and even more preferably 15 to 32.5%.

[0033] Mo: 0.1-8% Mo is an important element in the present invention. It plays a role in retarding the progress of pitting corrosion and improving corrosion resistance. Therefore, the content is specified to be 0.1 to 8%. It is preferably 0.5 to 7.5%, and more preferably 0.8 to 7.2%.

[0034] Cu: 0.1-4% Cu is an important element for improving acid resistance and sulfuric acid resistance and thus maintaining corrosion resistance, and also has the effect of softening in cold working, making it an extremely important element for deep drawing applications, etc. Therefore, the Cu content is specified to be 0.1 to 4%, preferably 0.5 to 3.5%, and more preferably 0.6 to 3.3%.

[0035] Al: 0.001 to 0.5% Al is a useful element for deoxidation. It also improves high-temperature oxidation resistance. On the other hand, if the content is too high, AlN is formed, impairing hot workability, and the Ca and Mg concentrations become too high, exceeding the upper limit of the range of the present invention. As a result, harmful CaO-based inclusions are formed, and a low-melting point compound called NiMg2 is formed, reducing hot workability. The deoxidation reaction proceeds as follows. 2 Al +3 O =(Al2O3) …(4) As will be described in detail later, by lowering the alumina activity in the slag, deoxidation proceeds efficiently. Furthermore, desulfurization also becomes possible at the same time. Therefore, the content is specified to be 0.001 to 0.5%. It is preferably 0.005 to 0.4%, more preferably 0.007 to 0.38%, and further preferably 0.01 to 0.35%.

[0036] Ti: 0.6% or less Ti is an important element for ensuring blackening properties in sheathed heater materials, and also forms fine G phases in high-strength materials to maintain high strength. However, if the content is too high, TiN and TiC are formed, which can cause surface defects. Therefore, the content is specified to be 0.6% or less. Preferably, it is 0.5% or less. More preferably, it is 0.45% or less.

[0037] Ca: 0.0001-0.02% Ca is an important element for controlling the structure of nonmetallic inclusions to the preferred CaO-Al2O3-MgO oxides. By controlling the structure in this way, it is possible to manufacture sound products without causing thrusters or forming surface defects. Ca is effectively added by utilizing the following reaction: 3(CaO)+2 Al =(Al2O3)+3 Ca …(5) 2(CaO)+ Si =(SiO2)+2 Ca …(6) To control this reaction, the activity of alumina and silica in the slag should be controlled within an appropriate range. This will be explained in detail in the manufacturing method. On the other hand, if the content is too high, harmful CaO inclusions are formed, which promotes clustering and creates defects. Therefore, the content is specified to be 0.0001 to 0.02%. The content is preferably 0.0005 to 0.015%, and more preferably 0.001 to 0.013%.

[0038] Mg: 0.0001-0.02% Mg is an important element for controlling the structure of nonmetallic inclusions to the preferred CaO-Al2O3-MgO oxide, MgO, and MgO·Al2O3. By controlling the structure in this way, it is possible to manufacture sound products without causing thrusters or forming surface defects. Mg is effectively added by utilizing the following reaction: 3(MgO)+2 Al =(Al2O3)+3 Mg …(7) 2(MgO)+ Si =(SiO2)+2 Mg …(8) To control this reaction, the activity of alumina and silica in the slag should be controlled within an appropriate range. This will be explained in detail in the manufacturing method. On the other hand, if it is too high, Mg vaporizes during solidification and forms blowholes, which in turn form surface defects. Therefore, the content is specified to be 0.0001 to 0.02%. It is preferably 0.0005 to 0.015%, and more preferably 0.001 to 0.013%.

[0039] N: 0.001 to 0.4% N is effective for stabilizing the austenite phase, and also plays a role in preventing pitting corrosion by bringing NH4Cl into pitting corrosion. Therefore, the range of N content is set to 0.001 to 0.4%, preferably 0.003 to 0.38%, and more preferably 0.004 to 0.37%.

[0040] O: 0.01% or less The oxygen content must be reduced because it increases the number of nonmetallic inclusions and forms surface defects. Therefore, the oxygen content is set to 0.01% or less. It is preferably 0.008% or less, more preferably 0.007% or less, and even more preferably 0.005% or less.

[0041] One or more of Co, W, Nb, and B should be 4% or less Co is an element effective in stabilizing the austenite phase. It is also sometimes contained in ferronickel alloys and pure Ni raw materials, and plays an important role in terms of utilizing inexpensive raw materials. W is a useful element for increasing corrosion resistance. Nb is useful because it is a component that forms the G phase in high-strength materials. B is an effective element for improving the creep properties of heat-resistant steel, and also improves hot workability. It is more preferable to contain one or more of these elements at 4% or less. In other words, they may be added as necessary.

[0042] The balance of the stainless steel of the present invention is iron. It may also contain trace amounts of unavoidable impurities, such as Pb, Sn, Ta, Ag, Na, K, and Zr. All of these are mixed in from the scraps that are the raw materials.

[0043] Next, the average composition of the nonmetallic inclusions will be described. The average composition of the nonmetallic inclusions is as follows: MgO: 30~70% MgO is effective for forming harmless CaO-Al2O3-MgO oxides, and is also extremely effective for forming simple MgO and simple MgO·Al2O3, which are similarly harmless. Therefore, the content is specified to be 30 to 70%. The preferred content is 35 to 65%.

[0044] Al2O3: 15-40% Al2O3 is effective for forming harmless CaO-Al2O3-MgO oxides, and is also extremely effective for forming MgO·Al2O3, which is also harmless. However, if it is higher than 40%, it forms harmful Al2O3 simple substance, which causes defects. Therefore, it is specified to be 15-40%. It is preferably 18-39%.

[0045] SiO2: 30% or less SiO2 is a compound present in CaO-Al2O3-MgO oxides, and is effective in lowering the melting point. However, if it exceeds 30%, the oxygen concentration tends to increase, which not only increases the number of nonmetallic inclusions but also forms harmful MnO-Cr2O3 oxides, resulting in defects. Therefore, it is specified to be 30% or less. Preferably, it is 28% or less.

[0046] CaO: 10-40% CaO is effective for forming harmless CaO-Al2O3-MgO oxides, but if the content is too high, harmful CaO inclusions are formed, resulting in defects. Therefore, the content is specified to be 10 to 40%. The content is preferably 12 to 39%. The content is more preferably 13 to 38%.

[0047] MnO: 1% or less MnO is harmless because it dissolves in the MgO sites of MgO and MgO·Al2O3 inclusions. However, if the content is too high, it forms harmful MnO-Cr2O3 oxides, which can cause defects. Therefore, the content is set at 1% or less. It is preferably 0.9% or less. It is more preferably 0.8% or less.

[0048] Cr2O3: 1.5% or less Although not particularly limited, a high Cr2O3 content makes it easier for MnO-Cr2O3-based inclusions to form. Furthermore, the oxygen concentration in the molten steel also increases, increasing the number of nonmetallic inclusions and causing defects. Therefore, it is preferable that the Cr2O3 content is 1.5% or less. More preferably, it is 1.3% or less. Even more preferably, it is 0.6% or less.

[0049] There are several methods for determining the average composition. It can be clarified by randomly analyzing 10 points using SEM / EDS. In this case, it is necessary to analyze two points on the periphery of the center, and the average can be obtained by taking a mapping and measuring the area ratio by image analysis. It is preferable to analyze 20 points or more, and more preferably 30 points or more. The other is the so-called electrolytic method, which is widely known as the Speed ​​method. In other words, the metal part is dissolved by applying an appropriate potential in an appropriate solution. After that, the non-metallic inclusions that become the residue are collected by filtration. The average composition can be obtained all at once by subjecting this to chemical analysis. There is no limitation on the analysis method.

[0050] Furthermore, the structural morphology of nonmetallic inclusions will be explained. In a more preferred embodiment, nonmetallic inclusions that account for 70% or more of the total number of nonmetallic inclusions are one or more of the following five types a to e. The structural morphologies corresponding to a to e are also shown in Figures 2(a) to (e). a: CaO-Al2O3-MgO oxide completely encloses MgO·Al2O3 within a roughly spherical surface b: CaO-Al2O3-MgO oxide c: CaO-Al2O3-MgO oxide completely encloses MgO within a roughly spherical surface d: MgO alone e: MgO·Al2O3 alone Here, being completely contained within an approximately spherical surface means that the internal material is completely contained within the material on the outer edge as shown in FIG. 1(a), and does not include a state in which the internal material partially protrudes to the outside as shown in FIG. 1(b).

[0051] As explained in the means for solving the problems, the form in FIG. 1(b) does not appear in the following operation. In order to control these structural forms, it is sufficient to control the chemical components Si, Al, Ca, Mg, O, and Mn within the range of the present invention, but this is not all. a and c are also characteristic of the present invention. In order to achieve these structural forms, the key points are after the decarburization process in AOD. During the Cr reduction period, quicklime is first added, and at the same time, fluorite and waste bricks containing MgO are added. After that, when ferrosilicon alloy and Al are added, Si and Al are added to the already formed molten slag. This directly reacts with CaO and MgO in the slag, and Ca and Mg can be effectively added.

[0052] Mg is supplied to the molten steel in advance according to the reactions of equations (7) and (8). The reason for this is unclear, but the reaction of Ca is delayed. This dissolved Mg reacts first with the original non-metallic inclusions, silica and alumina, as shown below. 2 Mg +SiO2(inclusion)=2MgO(inclusion)+2 Si …(9) 3 Mg +Al2O3(inclusion) = 3MgO(inclusion) + 2 Al …(10) 2 Mg +4 Al + 4SiO2(inclusions) = 2MgO·Al2O3(inclusions) + 4 Si …(11) 3 Mg + 4Al2O3(inclusions) = MgO·Al2O3(inclusions) + 2 Al …(12) As shown in formulas (9) to (12) above, simple MgO and simple MgO·Al2O3 are formed initially. After that, Ca is supplied from the slag, and the Ca in the molten steel reacts with the inclusions mentioned above, resulting in the vigorous formation of CaO-Al2O3-MgO oxides on the surface. These molten oxides then cover the simple MgO and simple MgO·Al2O3, rendering them harmless. In other words, they are molten and behave as harmless CaO-Al2O3-MgO inclusions. Therefore, if the non-metallic inclusions are spherical, they will behave as described above and will be harmless.

[0053] Furthermore, the composition range of the above CaO-Al2O3-MgO oxide will be explained. CaO: 20~60%, Al2O3: 30~60%, MgO: 1~30%, SiO2: 20% or less, TiO2: 0.5% or less The above range was set because it is possible to maintain the molten state of CaO-Al2O3-MgO oxides at the steelmaking temperature, i.e., near 1500°C. In particular, if the CaO content is too high, harmful simple CaO inclusions are formed, so CaO: 20-60% was specified. If the Al2O3 content is too high, simple Al2O3 is formed, so Al2O3: 30-60% was specified. If the SiO2 content is too high, harmful MnO-Cr2O3 inclusions are formed, so it was set to 20% or less.

[0054] MnO concentration in MgO·Al2O3: 0.5% or less Since MnO dissolves in the MgO sites of MgO·Al2O3, it is possible to render MnO harmless. Therefore, the content is set at 0.5% or less.

[0055] MgO simple inclusions contain Al2O3: 3% or less, SiO2: 1% or less, CaO: 10% or less, MnO: 1% or less Since MgO inclusions are harmless, it is desirable for them to dissolve in the inclusions to some extent. Taking into account the solubility limit, the contents are set at Al2O3: 3% or less, SiO2: 1% or less, CaO: 10% or less, and MnO: 1% or less.

[0056] The present invention also provides a manufacturing method. That is, the raw materials are melted in an electric furnace, and then decarburized and refined in an AOD. The raw materials may be stainless steel scrap, Ni, ferrosilicon alloy, ferrosilicon alloy, iron scrap, Mo, Mo trioxide, ferromolybdenum alloy, ferroniobium alloy, ferrochrome alloy, copper wire, etc., which may be blended according to the target steel type.

[0057] After the decarburization process is completed, the Cr in the molten steel is oxidized to form Cr2O3, so quicklime and FeSi are added to carry out Cr reduction according to the following reaction: 2(Cr2O3)+3 Si =3(SiO2)+4 Cr …(13)

[0058] Furthermore, Al is added to form CaO-Al2O3-MgO-SiO2-F slag, which is then deoxidized and desulfurized, and a slab is produced in a continuous casting machine. After the surface is ground, the slab is subjected to a hot rolling process and then cold rolling. At this time, in order to control the structure of the nonmetallic inclusions to a desirable form, it is necessary to control the slag composition within an appropriate range.

[0059] The following range is desirable for CaO-Al2O3-MgO-SiO2-F slag. CaO: 35-70% The CaO concentration can be adjusted by adding quicklime. CaO has a tremendous effect on deoxidation and desulfurization. In other words, as shown in formulas (2) and (3), desulfurization is possible by making CaO exist stably as CaS in the slag. However, if the CaO concentration is higher than 70%, CaO inclusions are formed. Therefore, 35 to 70% is preferable. Preferably, it is 40 to 65%. More preferably, it is 50 to 63%.

[0060] Al2O3: 30% or less Al2O3 is effective in making CaO-Al2O3-MgO-SiO2-F slag molten. On the other hand, if it exceeds 30%, it creates Al2O3 simple inclusions and promotes clustering. Therefore, it is desirable to keep it at 30% or less. Preferably, it is 25% or less. More preferably, it is 22% or less.

[0061] MgO: 3~25% MgO is effective in making CaO-Al2O3-MgO-SiO2-F slag molten. On the other hand, if the MgO concentration is high, the Mg concentration in the molten steel will be high, and Mg gas will be released during solidification, forming blowholes. Therefore, 3 to 25% is preferable. 5 to 20% is more preferable, and 7 to 15% is even more preferable.

[0062] SiO2: 3-32% SiO2 is effective for making CaO-Al2O3-MgO-SiO2-F slag into a molten state. On the other hand, if the SiO2 concentration is high, the oxygen concentration in the molten steel will be high, and the nonmetallic inclusion composition will also be MnO-Cr2O3-based. As a result, surface defects will occur. Therefore, 3-32% is preferable. 5-30% is more preferable. 5-20% is even more preferable.

[0063] F: 0.5 to 10% F is added as fluorite. F is effective in molten CaO-Al2O3-MgO-SiO2-F slag. On the other hand, if the F concentration is high, it will corrode the AOD bricks and ladle bricks, shortening their lifespan. Therefore, 0.5 to 10% is preferable. 1 to 9% is more preferable.

[0064] Furthermore, it is desirable that the Cr2O3 and FeO concentrations are low. Cr2O3: 1% or less If it is too high, the oxygen concentration will increase and cause the formation of MnO-Cr2O3-based inclusions. Therefore, it is best to keep it below 1%, preferably below 0.7%, and more preferably below 0.6%.

[0065] FeO: 1% or less If it is high, the oxygen concentration will be high and will cause the formation of MnO-Cr2O3-based inclusions. Therefore, it is best to keep it below 1%. Preferably, it is below 0.9%. More preferably, it is below 0.8%. Furthermore, it is better to have a high S concentration. This is because it indicates that desulfurization has progressed normally. It is preferable to keep it above 0.3%, and more preferably, above 0.4%. EXAMPLES

[0066] The effectiveness of the present invention will be clarified by showing examples below. 70 tons of raw materials were melted in an electric furnace, and then decarburized and refined in an AOD. The raw materials were stainless steel scrap, Ni, ferrosilicon alloy, ferrosilicon alloy, iron scrap, Mo, Mo trioxide, ferromolybdenum alloy, ferroniobium alloy, ferrochrome alloy, copper wire, etc., blended according to the target steel type. After the decarburization process was completed, the Cr2O3 that had moved into the slag was reduced. That is, quicklime and waste bricks containing magnesia, and then fluorite were added, and then FeSi was added. This reduced the Cr oxide in the slag, completing the Cr reduction process in which the valuable metal Cr was returned to molten steel. Furthermore, Al was added to some steel types, and finally a CaO-Al2O3-MgO-SiO2-F slag was formed. Even when Al was not added, the impurity Al in the FeSi alloy was oxidized to supply alumina.

[0067] For some steel types, alloy elements such as Nb, Mo, C, Co, Cr, B, and Ni were added to precisely adjust the chemical composition. After deoxidization and desulfurization, slabs of 200 mmt x 1200 mmw x 7 m length were produced using a continuous casting machine, and the oscillation marks on the surface were ground. After heating to 1150 to 1250°C depending on the steel type, the slabs were subjected to a hot rolling process, and finally cold rolling was performed and passed through an annealing and pickling line. In this way, 1 mm cold rolled coils were produced for all steel types.

[0068] At this time, the evaluation was carried out by the following methods. 1) Chemical composition: The surface of a 30mm diameter x 10mm high suction sample taken from the tundish of the continuous casting machine was ground with a grinder. Major elements were analyzed by fluorescent X-ray analysis. Some C and S were analyzed by the combustion method. N and O were also analyzed by the infrared absorption method. Furthermore, H values ​​were obtained using a hydrogen analyzer. 2) Slag components: Slag was collected with an iron bar and crushed. This was then pressed into a cylindrical sample. The values ​​of this sample were determined using X-ray fluorescence analysis. F was determined by chemical analysis. 3) Average composition of non-metallic inclusions: The above-mentioned suction sample was cut out, embedded in resin, and mirror-polished. This was then placed in an SEM for observation and quantitative analysis. Thirty inclusions of 5 μm or more were randomly selected, and the center and periphery were analyzed. The element distribution of each inclusion was determined by mapping, and the ratio of each phase was calculated by image analysis. Taking into account the weighted average, a representative analysis value of each inclusion particle was obtained. This was determined by calculating the average value of the 30 points. 4) Morphology of nonmetallic inclusions: The morphology was classified when observed and analyzed as described above. The morphology shown on the right side of Figure 1 was not confirmed. 5) Composition of each oxide: Calculated from the composition of each oxide phase described above. 6) Overall evaluation: An inspector visually evaluated a 1mm thick stainless steel plate when it was threaded. The evaluation results were determined as follows. The allowable range for not cutting the steel plate is within 10 mm of the surface of the plate. 2 This means that there are up to three linear scratches of 1mm or more in length per unit area. Passed: No surface defects (100% non-defective product at time of shipment) Passed: Some surface defects occurred but within the required quality tolerance (95% pass rate). Pass: △ Surface defects occurred in some areas, but the product can be shipped after partial cutting (80% pass rate) Rejected: × Surface defects occurred along the entire length of the coil, and the coil was scrapped (0% defective product rate).

[0069] [Table 1]

[0070] [Table 2]

[0071] The structural morphologies of the examples are shown in Figures 2(a) to (e), and those of the comparative examples are shown in Figures 2(f) to (h). For invention examples Nos. 1 to 14, the chemical analysis was within the range, and the slag composition also met the desired range. As a result, the structural morphology of the nonmetallic inclusions also met the range of a to e. Ultimately, all of the products were judged to be acceptable.

[0072] However, one alumina inclusion and one MnO-Cr2O3 inclusion were confirmed in No. 5 and 10. One simple CaO inclusion was observed in No. 8. Therefore, the evaluation was ◯. Furthermore, in No. 11, the MnO concentration in the MgO·Al2O3 was high, and the SiO2 and MnO in the MgO inclusions were high, while simple CaO inclusions, simple Al2O3 inclusions, and MnO-Cr2O3 inclusions were confirmed. As a result, the evaluation was △.

[0073] Next, a comparative example will be described. No.15 had low Si. Conversely, Al was high and the CaO concentration in the slag exceeded the desired range, resulting in high Ca and Mg concentrations. As a result, MgO and CaO were not included in the average composition of the inclusions. The structure also had more f·CaO alone, with the CaO in the CaO-Al2O3-MgO oxides being high. In other words, the CaO alone inclusions became the center, causing defects and resulting in scrapping.

[0074] In No. 16, the Si concentration was too high, which resulted in high Ca and Mg concentrations. The high Si concentration also led to a high SiO2 concentration in the slag. The F concentration was also low, resulting in a lack of slag fluidity. The Ti concentration was also too high, resulting in the formation of TiN clusters. In terms of the average composition of the inclusions, MgO and CaO were out of range, and the alumina, MgO, and SiO2 in the CaO-Al2O3-MgO oxide system were out of range, and the structural morphology also showed the formation of many simple f·CaO inclusions. The formation of many simple TiN and CaO inclusions caused numerous surface defects, resulting in the coil becoming scrap.

[0075] In No.17, the Si content was low and Al was not included, which resulted in low Ca and Mg concentrations, and the oxygen concentration was high, resulting in a large number of non-metallic inclusions. In addition, the slag composition was also out of range, with high silica and high CaO, which had a negative effect on the inclusion composition. The average composition of the inclusions was out of range for all oxides, and the microstructure also showed the formation of many h·MnO-Cr2O3-based inclusions. Alumina and silica were also not included in the CaO-Al2O3-MgO-based oxide, and MnO-Cr2O3-based inclusions were confirmed. As a result, surface defects occurred along the entire length, resulting in scrapping.

[0076] No.18 had a high Al concentration, resulting in a high alumina concentration in the slag, while the CaO concentration was low. The average composition of the nonmetallic inclusions was 100% alumina, and the microstructure consisted of only g·Al2O3 inclusions. As a result, surface defects occurred along the entire length, resulting in scrapping.

[0077] No.19 had a low Al concentration, which resulted in low Ca and Mg concentrations and a high oxygen concentration, which was off the mark. The average composition of the nonmetallic inclusions was high in Cr2O3, and the three types of structure f, g, and h were frequently formed. In particular, many h·MnO-Cr2O3 inclusions were observed. Furthermore, simple MgO·Al2O3 inclusions and components that form a solid solution in simple MgO inclusions were also off the mark. In addition, the Ti and N concentrations were high, and TiN clusters were also observed. As a result, surface defects occurred along the entire length, causing scrapping.

[0078] No. 20 had high Cr and C contents, which caused severe embrittlement and meant it could not be shipped as wear-resistant steel and was scrapped.

Claims

1. The alloy contains, in mass %, C: 0.001-0.3%, Si: 0.1-4%, Mn: 0.1-3%, P: 0.05% or less, S: 0.03% or less, Ni: 4-40%, Cr: 13-35%, Mo: 0.1-8%, Cu: 0.1-4%, Al: 0.001-0.5%, Ti: 0.6% or less, Ca: 0.0001-0.02%, Mg; 0.0001-0.02%, N: 0.001-0.4%, O: 0.01% or less, and one or more of Co, W, Nb, and B in an amount of 4% or less, with the balance being iron and unavoidable impurities. The average composition of the non-metallic inclusions is MgO: 30-70%, Al: 0.001-0.02%, Mg: 0.0001-0.02%, N: 0.001-0.4%, and O: 0.01% or less. 2 O 3 :15-40%, SiO 2 : 30% or less, CaO: 10 to 40%, MnO: 1% or less.

2. The stainless steel having excellent surface properties as described in claim 1, characterized in that the structural form of the non-metallic inclusions is such that 70% or more of the non-metallic inclusions in terms of number ratio to the total non-metallic inclusions are any one or more of the following five types a to e. a: CaO-Al 2 O 3 -MgO-based oxide is MgO.Al within the approximately spherical surface 2 O 3 A form that completely encompasses b: CaO-Al 2 O 3 -MgO acid compound c: CaO-Al 2 O 3 - A form in which MgO-based oxide completely encapsulates MgO within a substantially spherical surface d: MgO alone e: MgO.Al 2 O 3 Single

3. The CaO—Al 2 O 3 -MgO-based oxides are CaO: 20-60%, Al 2 O 3 :30~60%, MgO:1~30%, SiO 2 :20% or less, TiO 2 3. The stainless steel having excellent surface properties as claimed in claim 2, characterized in that the content of C is 0.5% or less.

4. The MgO.Al 2 O 3 3. The stainless steel having excellent surface properties according to claim 2, characterized in that it contains 0.5% or less of MnO.

5. The MgO simple substance is Al 2 O 3 :3% or less, SiO 2 3. The stainless steel according to claim 2, further comprising: ZnO: 1% or less, CaO: 10% or less, and MnO: 1% or less.

6. The method for producing stainless steel according to any one of claims 1 to 5, comprising the steps of melting raw materials in an electric furnace, decarburizing and refining the raw materials using an AOD, adding quicklime and FeSi to carry out Cr reduction, and then adding Al to form a CaO-Al 2 O 3 -MgO-SiO 2 A method for producing stainless steel with excellent surface properties, characterized in that F-based slag is formed, deoxidized and desulfurized, a slab is produced using a continuous casting machine, the surface is ground, and then a hot rolling process is performed, followed by cold rolling.

Citation Information

Patent Citations

  • Belt for continuously variable transmission, and stainless steel therefor

    JP2005290450A

  • HIGH CORROSION RESISTANT Ni-Cr-Mo STEEL EXCELLENT IN WELDABILITY AND SURFACE PROPERTY, AND METHOD FOR MANUFACTURING THE SAME

    JP2021031720A

  • Stainless steel having excellent surface properties and method for producing the same

    JP2021107571A

  • Stainless steel, stainless steel material, and stainless steel production method

    WO2021172378A1

  • Duplex stainless steel wire rod, and duplex stainless steel wire

    WO2022210651A1